Comprehensive Chemical Profiling and Multidirectional Biological Investigation of Two Wild Anthemis Species (Anthemis tinctoria var. Pallida and A. cretica subsp. tenuiloba): Focus on Neuroprotective Effects - ŞENKARDEŞ, İSMAİL (MDPI, 2019)
Ethyl acetate (EA), methanol (MeOH), and aqueous extracts of aerial parts of Anthemis tinctoria var. pallida (ATP) and A. cretica subsp. tenuiloba (ACT) were investigated for their phenol and flavonoid content, antioxidant, and key enzyme inhibitory potentials. All extracts displayed antiradical effects, with MeOH and aqueous extracts being a superior source of antioxidants. On the other hand, EA and MeOH extracts were potent against AChE and BChE. Enzyme inhibitory effects against tyrosinase and alpha-glucosidase were observed, as well. We also studied Anthemis extracts in an ex vivo experimental neurotoxicity paradigm. We assayed extract influence on oxidative stress and neurotransmission biomarkers, including lactate dehydrogenase (LDH) and serotonin (5-HT), in isolated rat cortex challenged with K+ 60 mM Krebs-Ringer buffer (excitotoxicity stimulus). An untargeted proteomic analysis was finally performed in order to explore the putative mechanism in the brain. The pharmacological study highlighted the capability of ACT water extract to blunt K+ 60 mM increase in LDH level and 5-HT turnover, and restore physiological activity of specific proteins involved in neuron morphology and neurotransmission, including NEFMs, VAMP-2, and PKC gamma, thus further supporting the neuroprotective role of ACT water extract.
Keywords: Anthemis; oxidative stress; neurotransmission; proteomic; phytomedicine; ESSENTIAL OIL; ANTIMICROBIAL ACTIVITY; TRANSIENT INCREASE; IMMUNOREACTIVITY; SYNAPTOSOMES; ANTIOXIDANT; MONOAMINES; HYPOXIA; ACID